DOPUSZCZALNOŚĆ ROSZCZEŃ REGRESOWYCH INSTYTUCJI ZABEZPIECZENIA SPOŁECZNEGO Z PAŃSTW UNII EUROPEJSKIEJ WOBEC POLSKIEGO UBEZPIECZYCIELA OC UBEZPIECZONEGO – ODPOWIEDZIALNEGO ZA SZKODĘ - Fuchs, Dariusz (Zeszyty Prawnicze, 2016)
Admissibility of Claims of Social Security Institutions of the European Union Countries to the Polish Insurer of Civil Liability Insured who is Responsible for the Damage Summary The paper contains a general overview of the legal nature and the specific character of the recourse under the EU regulations on the application of social security schemes to employed persons and their families moving within the EU concerning civil liability insurer. It was underlined specific position of the social insurance institutions form EU Members versus Polish insurer. It was expressed that necessity of amendment of the Polish insurance regulation to create a base for recourse as in EU regulation.